Dopaminergic medication reduces interhemispheric hyper-synchronization in Parkinson's disease. (April 2022) - Koren, Or; Bartsch, Ronny P.; Katzir, Zoya; Rosenblum, Uri; Hassin-Baer, Sharon; Inzelberg, Rivka; Plotnik, Meir
Abstract: Introduction: We previously reported on interhemispheric cortical hyper synchronization in PD. The aim of the present study was to address the hypothesis that increased interhemispheric cortical synchronization in PD is related to dopamine deficiency and is correlated with motor function. Methods: We studied participants with PD and characterized cortical synchronization with reference to brain regions. Electroencephalography (EEG) was recorded from 20 participants with PD while OFF and ON their dopaminergic medications (two separate visits), during quiet standing and straight-line walking. Cortical interactions in the theta, alpha, beta, and gamma brain wave frequency bands were evaluated using interhemispheric phase synchronization (inter-PS). Results: Inter-PS values were found to be significantly higher during the OFF state as compared to the ON state in standing and walking trials for theta, alpha and beta bands. In addition, inter-PS reduction from OFF to ON was associated with mobility improvement evaluated by the Timed Up and Go test, and with daily levodopa equivalent dose across individuals. Higher differences in inter-PS values between OFF and ON states were evident mainly in the occipital-parietal cortex. Conclusions: Persons with PD have increased inter-PS during the OFF state compared to their ON state, and this increase in inter-PS is associated with the clinical improvement between OFF and ON. We speculate that these findings, together with previous evidence of higher inter-PS in PD as compared to healthy older adults, reflect neuronal processes consequential to asymmetric subcortical dopamine deficiency. Highlights: EEG signals were recorded during standing and walking in persons with PD. Inter-hemispheric synchronization was compared between OFF and ON medications. Increased inter-hemispheric EEG synchronization was observed in OFF as compared to ON. Improvement in motor symptoms during ON was associated with the reduction in EEG synchronization.